2016
DOI: 10.15537/smj.2016.11.15268
|View full text |Cite
|
Sign up to set email alerts
|

The Saudi clinical practice guideline for the prophylaxis of venous thromboembolism in medical and critically ill patients

Abstract: Venous thromboembolism (VTE) acquired during hospitalization is common, yet preventable by the proper implementation of thromboprophylaxis which remains to be underutilized worldwide. As a result of an initiative by the Saudi Ministry of Health to improve medical practices in the country, an expert panel led by the Saudi Association for Venous Thrombo Embolism (SAVTE; a subsidiary of the Saudi Thoracic Society) with the methodological guidance of the McMaster University Guideline working group, produced this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
(52 reference statements)
0
19
0
Order By: Relevance
“…Recently, the Saudi Ministry of Health has endorsed national clinical practice guidelines on thromboprophylaxis. [ 31 ] Healthcare administrative authorities should assess the effectiveness of selected strategies as modifications may be needed depending on results. We found that surgical patients received thromboprophylaxis significantly more often than medical patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Saudi Ministry of Health has endorsed national clinical practice guidelines on thromboprophylaxis. [ 31 ] Healthcare administrative authorities should assess the effectiveness of selected strategies as modifications may be needed depending on results. We found that surgical patients received thromboprophylaxis significantly more often than medical patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1] The general administration of pharmaceutical care shared in publications of those guidelines. [2][3] The administration started evidence-based pharmacy system in early 2015 through drug information center. [4] Several national pharmacy practice programs implemented at Ministry of health hospitals including stewardship antimicrobial program, anticoagulation system and pain management services.…”
Section: Introductionmentioning
confidence: 99%
“…The teams finished from several guidelines for instance but not limited to anticoagulation surgical prophylaxis in critically ill patients, anticoagulation surgical prophylaxis of extended travel and chronic illness. [10,11] There were programs engrossed on cost-related issues, for instance, Pharmacoeconomics programs, a cost avoidance of medication error prevention, a cost avoidance of drug information centers, a cost avoidance of pharmacist intervention and cost also preventable of pharmacist running Total Parental Nutrition (TPN). [10][11][12] The primary objective of the program was to recognize and prevent drug-related problems; through healthcare provider's awareness towards medications.…”
Section: Discussionmentioning
confidence: 99%
“…The Healthcare professional knowledge about prescribed medication is a vital factor in decisive their compliance a patient and outcome of a disease. [11,12] The healthcare providers can improve pharmacist communication skills with enough proving of medications knowledge and patient education about medications. The implementation of pharmaceutical care concept is highly challenging for healthcare professionals and drug information resources should be available to all healthcare providers.…”
Section: Discussionmentioning
confidence: 99%